ANALISIS SWOT DAN STRATEGI PEMASARAN SYARIAH PADA UD R_DESIGN PRINTING - Yeni Rokhilawati; Nurul Hidayah (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2025)
ABSTRACT The printing business is a business that has a wide scope, this business can include graphic design, screen printing, digital printing, print media and advertising. There are many printing businesses spread across Indonesia that provide different services and products, ranging from those that specialize in just one service/product to businesses that provide almost all services and products. The large number of printing businesses currently creates a lot of competition, so printing business owners must be able to create a good strategy to face this competition.This research aims to explain how to analyze SWOT (Strengths, Weaknesses, Opportunities, Threats) and Marketing Strategy in a Micro, Small and Medium Enterprise (UMKM), namely a Printing Business which is managed by an individual by analyzing the internal and external factors of a business and how the business works. in carrying out marketing strategies.The results of this research show that the result of the SWOT Analysis are that R_Design Printing has several points which are divided into 2 internal and external factors consist of 2 elements, namely Strenghts and Weaknesses. And also external factors which consist of 2 elements, namely Opportunities and Threats. Apart from analyzing SWOT, this research also explains the Sharia Marketing Strategy at R_Design Printing using the 9P’s Marketing Mix.